TAYANCH MA’NAVIY KOMPETENSIYALAR VOSITASIDA 1-SINF OʻQUVCHILARIDA IJTIMOIY KREATIVLIKNI RIVOJLANTIRISH USULLARI (“Yangi avlod” darsliklari misolida) - Raximova, M.A. (SCIENCE and SOCIETY, 2024)
This article examines the current textbooks “Yangi avlod” and describes methodological techniques for developing students’ social creativity with the help of basic spiritual competencies in teaching Education lessons in 1-grade. In addition, the author mentioned the social-emotional skills that need to be developed in students through teaching the subject of Parenting in 1-grade.